Improving elementary school students’ self-regulated learning through growth mindset psychoeducation - Alexander, Angelita Asafani; Rohinsa, Meilani; Megarini, M. Yuni (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
This study examines the effectiveness of growth mindset psychoeducation using a quasi-experimental one-group pretest-posttest design involving 18 sixth-grade students at "X" elementary school, Bandung. Results showed significant improvement in self-regulated learning (SRL) forethought (Z = -2,74 p < 0,05) and a significant influence of growth mindset on SRL (R² = 0,636 F = 27,97 p < 0,01). This study provides insight that growth mindset can enhance forethought phase, helping students facing transition. Elementary school students should apply growth mindset strategies, such as setting SMART goals, while schools should support these efforts. Future research should include control groups and parental perspectives.